Protective effects of melatonin against oxidative stress in Fmr1 knockout mice: a therapeutic research model for the fragile X syndrome - Romero-Zerbo, Silvana Yanina; Decara, Juan; El Bekay Rizky, Rajaa; Sánchez-Salido, Lourdes; Del Arco-Herrera, Ignacio; Rodriguez-de-Fonseca, Fernando; De-Diego-Otero, María Yolanda (Blackwell Munksgaard, 2009)
Fragile X syndrome is the most common form of inherited mentalretardation. It is typically caused by a mutation of the Fragile X mental-retardation 1 (Fmr1) gene. To better understand the role of the Fmr1 geneand its gene product, the fragile X mental-retardation protein in centralnervous system functions, an fmr1 knockout mouse that is deﬁcient in thefragile X mental-retardation protein was bred. In the present study, fragile Xmental retardation 1-knockout and wild-type mice are used to determinebehaviour and oxidative stress alterations, including reduced glutathione,oxidized glutathione and thiobarbituric acid-reactive substances, before andafter chronic treatment with melatonin or tianeptine. Reduced glutathionelevels were reduced in the brain of fmr1-knockout mice and chronicmelatonin treatment normalized the glutathione levels compared withthe control group. Lipid peroxidation was elevated in brain and testes offmr1-knockout mice and chronic melatonin treatment prevents lipidperoxidation in both tissues. Interestingly, chronic treatment with melatoninalleviated the altered parameters in the fmr1-knockout mice, includingabnormal context-dependent exploratory and anxiety behaviours andlearning abnormalities. Chronic treatment with tianeptine (a serotoninreuptake enhancer) did not normalize the behaviour in fmr1-knockout mice.The prevention of oxidative stress in the fragile X mouse model, by anantioxidant compound such as melatonin, emerges as a new and promisingapproach for further investigation on treatment trials for the disease
Keywords: Melatonina; Sistema nervioso central; Estrés oxidativo; Fragile X syndrome; Melatonin; Oxidative stress; Central nervous system; Antioxidant compound